The Effect of FoMO (Fear of Missing Out) on Purchasing Behavior in Public Relations Practices - Müge Bekman (Selçuk İletişim)
Technology has been developing rapidly for a very long time, and this development creates new dynamics in all areas of life. Now, there is almost no area independent from the phenomenon of technology and technological tools. In this context, public relations practices also try to influence people’s purchasing behavior through different tools and applications. Since public relations cannot be considered only as a promotional and image activity, the relationship of the issue with purchasing practices is established in this study. On the other hand, people’s buying behavior is influenced by certain methods. The aim of this article is to examine the effect of fear of missing out (FoMO) on developments, which is a new concept in public relations practices, on individuals’ purchasing behavior through the example of Trendyol. In this study, the extent to which the consumer's FoMO on the activities and life experiences of others affects their purchasing behavior is discussed. At the same time, how demographic structure affects purchasing behavior is also examined. The method of the study is structural equation modeling from a statistical point of view. The results of the study show that the increase in the fear of missing out affects purchasing behavior. It has been observed that this does not differ according to gender but differs according to education level and income source.Keywords: Public Relations, Fear of Missing Out (FoMO), Purchasing Behavior